CURRENT PROBLEMS OF CONCEPT RESEARCH IN MODERN PHILOLOGY IN THE CONTESXT OF GLOBAL TRANSMISSION - Волкова , Елена (Scientific practical conference, 2025)
the article examines the key challenges facing cognitive linguistics and philology in the field of concept research in the era of global transformations. It analyzes the impact of digitalization, cultural hybridization, socio-political changes, and the "war of meanings" on the structure and content of key concepts. The author concludes that modern philology requires an interdisciplinary approach and new methodological tools to adequately describe the dynamically changing conceptosphere.